Consensus-based recommendations for diagnosis and surgical management of cranioplasty and post-traumatic hydrocephalus from a European panel - Iaccarino, Corrado (Elsevier, 2026)
Introduction
Planning cranioplasty (CPL) in patients with suspected or proven post-traumatic hydrocephalus (PTH) poses a significant management challenge due to a lack of clear guidance.
Research question
This project aims to create a European document to improve adherence and adapt to local protocols based on available resources and national health systems.
Methods
After a thorough non-systematic review, a steering committee (SC) formed a European expert panel (EP) for a two-round questionnaire using the Delphi method. The questionnaire employed a 9-point Likert scale to assess the appropriateness of statements inherent to two sections: "Diagnostic criteria for PTH" and "Surgical strategies for PTH and cranial reconstruction."
Results
The panel reached a consensus on 29 statements. In the "Diagnostic criteria for PTH" section, five statements were deemed "appropriate" (consensus 74.2−90.3 %), two were labeled "inappropriate," and seven were marked as "uncertain."
In the "Surgical strategies for PTH and cranial reconstruction" section, four statements were considered "appropriate" (consensus 74.2−90.4 %), six were "inappropriate," and five were "uncertain."
Discussion and conclusion
Planning a cranioplasty alongside hydrocephalus remains a significant challenge in neurosurgery. Our consensus conference suggests that, in patients with cranial decompression and suspected hydrocephalus, the most suitable diagnostic approach involves a combination of evolving clinical conditions and neuroradiological imaging. The recommended management sequence prioritizes cranial reconstruction, with the option of a ventriculoperitoneal shunt when needed, preferably with a programmable valve. We strongly recommend to adopt local protocols based on expert consensus, such as this, to guide patient care.